A Receptor's Tale: An Eon in the Life of a Trypanosome Receptor. - Matthew K Higgins; Harriet Lane-Serff; Paula MacGregor; Mark Carrington (PLoS Pathogens)
African trypanosomes have complex life cycles comprising at least ten developmental forms, variously adapted to different niches in their tsetse fly vector and their mammalian hosts. Unlike many other protozoan pathogens, they are always extracellular and have evolved intricate surface coats that allow them to obtain nutrients while also protecting them from the immune defenses of either insects or mammals. The acquisition of macromolecular nutrients requires receptors that function within the context of these surface coats. The best understood of these is the haptoglobin-hemoglobin receptor (HpHbR) of Trypanosoma brucei, which is used by the mammalian bloodstream form of the parasite, allowing heme acquisition. However, in some primates it also provides an uptake route for trypanolytic factor-1, a mediator of innate immunity against trypanosome infection. Recent studies have shown that during the evolution of African trypanosome species the receptor has diversified in function from a hemoglobin receptor predominantly expressed in the tsetse fly to a haptoglobin-hemoglobin receptor predominantly expressed in the mammalian bloodstream. Structural and functional studies of homologous receptors from different trypanosome species have allowed us to propose an evolutionary history for how one receptor has adapted to different roles in different trypanosome species. They also highlight the challenges that a receptor faces in operating on the complex trypanosome surface and show how these challenges can be met.